The Effect of Unemployment Rate and Human Development Index (HDI) on Economic Growth in North Sumatra Province 2009-2024 - Dhea, Titian; Suharianto, Joko (Outline Journal of Management and Accounting, 2026)
This study aims to analyze the effect of the unemployment rate and the Human Development Index (HDI) on economic growth in North Sumatra Province during the period 2009–2024. This research employs a quantitative approach using time series data and multiple linear regression analysis. Economic growth is used as the dependent variable, while the unemployment rate and HDI serve as independent variables. The data were obtained from the Central Bureau of Statistics (BPS) and analyzed using EViews 11. The results indicate that the unemployment rate has a negative and significant effect on economic growth, while HDI has a positive and significant effect. Simultaneously, both variables also have a significant effect on economic growth. The model is able to explain a substantial proportion of the variation in economic growth, while the remaining variation is influenced by other factors outside the model. These findings highlight the importance of integrated policies in job creation and human development to promote sustainable economic growth.